2006
DOI: 10.1002/dvdy.20663
|View full text |Cite
|
Sign up to set email alerts
|

Spatial relations between avian craniofacial neural crest and paraxial mesoderm cells

Abstract: Fate maps based on quail-chick grafting of avian cephalic neural crest precursors and paraxial mesoderm cells have identified the majority of derivatives from each population but have not unequivocally resolved the precise locations of and population dynamics at the interface between them. The relation between these two mesenchymal tissues is especially critical for the development of skeletal muscles, because crest cells play an essential role in their differentiation and subsequent spatial organization. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
178
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 162 publications
(188 citation statements)
references
References 95 publications
(133 reference statements)
9
178
1
Order By: Relevance
“…6, 7; see also Fig. 10;Wahl et al, 1994;Evans and Noden, 2006). These studies identified progenitors for endothelial cells, smooth muscles, and a wide range of connective tissues in addition to skeletal muscles within paraxial mesoderm.…”
Section: Paraxial Mesodermmentioning
confidence: 82%
See 3 more Smart Citations
“…6, 7; see also Fig. 10;Wahl et al, 1994;Evans and Noden, 2006). These studies identified progenitors for endothelial cells, smooth muscles, and a wide range of connective tissues in addition to skeletal muscles within paraxial mesoderm.…”
Section: Paraxial Mesodermmentioning
confidence: 82%
“…However, other researchers have been unable to visualize somitomeres (Wachtler and Jacob, 1986) and, thus far, no molecular evidence of a segmental organization within this mesoderm has been found (Freund et al, 1996). Moreover, the initial sites of specific muscle, cartilage, and bone determination do not correspond to individual somitomeres (Noden, 1983b;Couly et al, 1992;Evans and Noden, 2006). Comparative analyses show that the position of specific somitomeres relative to other axial structures, specifically mid-and hindbrain segments, is not constant among embryos of the different vertebrate classes thus far examined.…”
Section: Paraxial Mesodermmentioning
confidence: 99%
See 2 more Smart Citations
“…This analysis revealed that Tbx1 transcripts are clearly apparent in the mesoderm adjacent to the caudal hindbrain from stage 7, encompassing the region that will give rise to the first and second arch muscles and the lateral rectus muscle (Fig. 3A, black arrow and data not shown; Evans and Noden, 2006; reviewed by Noden and Francis-West, 2006). In contrast, capsulin expression was undetectable in the cranial mesoderm ( Fig.…”
Section: Expression Analysis Of Tbx1 During Craniofacial and Limb Devmentioning
confidence: 88%